Developing an integrated conceptual framework of NewWork-settings: a systematic scoping review - Wawera, Anna-Sophia; Niebuhr, Fiona; Glaser, Sophie; Rinne, Carla; Voelter-Mahlknecht, Susanne (Frontiers in Sociology, 2025)
IntroductionThe last few decades have seen drastic changes in the world of work. These global transformations of work towards more digital, decentralized and democratic forms are commonly referred to as NewWork (NW). NW is frequently described as a container term encompassing a broad set of concepts. In order to provide conceptual clarity, the aim of this review was to develop an integrated conceptual framework of NW-settings, i.e., workplaces that have implemented different NW measures.MethodsA systematic scoping review was conducted, following the framework by Arksey and O’Malley and the Joanna Briggs Institute.ResultsBased on the synthesis of 99 included articles, we developed a multidimensional conceptual framework of NW-settings, which consists of four dimensions: flexibility, digitalization, democratization and agility, and 14 inter-related sub-dimensions.DiscussionThis framework facilitates a clearer understanding of NW and provides valuable insights for contemporary work practices and the broader social implications of digital and organizational transformations in our world of work.